Auxiliary-system-based composite adaptive optimal backstepping control for uncertain nonlinear guidance systems with input constraints. (December 2020) - Sun, Jingliang; Liu, Chunsheng
Abstract: This paper addresses a missile–target interception guidance process considering acceleration saturation and target maneuver as a constrained nonlinear tracking issue. A dynamic auxiliary system is designed for compensating the effects of constrained input, and external disturbances are counteracted through designing a nonlinear disturbance observer (NDO). The feedforward+feedback composite architecture is built in which a feedforward backstepping control and a feedback optimal control is presented recurrently. Furthermore, the parameter adaptive updating laws are derived to estimate the unknown functions online. Subsequently, the boundedness of the closed-loop signals are guaranteed. The predefined cost function is also ensured to be minimized. Furthermore, the control input is prevented violating its boundary. The contrastive simulation results demonstrate that the robustness of the proposed method is more superior to the nonsingular terminal sliding mode (NTSM) and the proportional navigation (PN) methods. Highlights: A feedforward+feedback control structure is built to ensure system's stability and optimality. The disturbance and input constraint are tackled simultaneously to improve the robustness. An online adaptive optimal guidance law is designed to improve the guidance performance